Policy responses to Turkey's crisis: Independent central bank and international credit - Alexander Kriwoluzky; Malte Rieth (DIW Weekly Report, 2018)
The presently tenuous situation in Turkey will worsen if the government does not take appropriate policy action. In view of foreign investors' loss of confidence, the cost of external financing is likely to rise while consumption and investment will fall, and the Turkish lira would depreciate further. The influx of foreign capital would dry up as well. Conservative estimates show that the country's growth would decline by five percent in the first year. These are the results of simulations with an equilibrium model developed by the German Institute for Economic Research. However, adopting measures such as budget consolidation, interest rate hikes, or lowering the target inflation rate could prevent a crisis. The most effective and efficient measure is lowering the perceived inflation target by restoring central bank's independence, thereby regaining investor confidence. Loans from international partners would also stabilize Turkey's currency, inflation, and economy - and support the country's reform process.
Keywords: E52; E58; F31; 330; monetary policy; exchange rates; fiscal policy; inflation targeting; emerging markets